Analysis and Valuation of Tesla Inc. - Hubka, Jakub (2018)
The aim of this diploma thesis is to analyze and understand Tesla Inc. business, identify its perspective and determine its intrinsic value. The date of valuation was set to 30 June 2018. In the first chapter I have described the company and its products. Next, I have performed financial and strategic analysis to determine Tesla Inc. financial position and its position within the industry. For the valuation I have used discounted cash flow model in the entity variant (DCF entity) as the most suitable valuation method for Tesla Inc. To check and support the valuation, I have performed supportive valuation based on market multiples. Lastly, sensitivity analysis was performed for a better understanding of the key inputs used in the DCF entity model.